Чевенгур - Платонов Андрей Платонович (Куйбышевское книжное издательство, 1990)
Экземпляры: ф.23 (2004) / Инвентарный номер: 47886 / Цена: / Сис.шифр: 84(2Рос=Рус)6-4 / Авт.знак: П 37 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6-4